2018
DOI: 10.1111/rec.12660
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of tropical montane cloud forests: a six‐prong strategy

Abstract: Tropical Montane Cloud Forests (TMCFs) are among the vegetation types facing the greatest threats, both globally and in Mexico. Ecological restoration of TMCFs is a priority in several tropical countries. In this paper, we propose that restoration of TMCFs based on applied nucleation methods should be accompanied by a set of additional mechanisms that form a six-prong strategy. In our experience, the essential set of tools to ensure positive results is composed of (1) a diagnostic-prescriptive stage;(2) specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
(26 reference statements)
1
19
0
Order By: Relevance
“…In their response to our recent paper (Ramírez‐Soto et al ), Holl and Zahawi () raise some points of agreement with our applied nucleation restoration approach. Our paper offers a six‐prong strategy for restoring tropical montane cloud forests (TMCF) based on our experience in Mexico.…”
supporting
confidence: 55%
“…In their response to our recent paper (Ramírez‐Soto et al ), Holl and Zahawi () raise some points of agreement with our applied nucleation restoration approach. Our paper offers a six‐prong strategy for restoring tropical montane cloud forests (TMCF) based on our experience in Mexico.…”
supporting
confidence: 55%
“…Applied nucleation studies were often conducted in tropical forests, and strip‐seeding and slot‐seeding studies most commonly occurred in temperate grasslands or pastures (Table S1). While methods of spatially patterned restoration are commonly described as “cost‐saving,” only two applied nucleation studies (Holl et al 2011; Ramírez‐Soto et al 2018) and one strip‐seeding study (Fry et al 2007) calculated costs of implementation. There were no studies that conducted a cost–benefit analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Only one applied nucleation study specifically focused on the effects of management on restoration outcomes and found that fertilization and trimming of herbaceous vegetation increased sapling growth rate, rate of expansion into the unplanted matrix, and species diversity (Dendy et al 2015). Only two studies reported costs, which were associated with planting and management (Holl et al 2011; Ramírez‐Soto et al 2018).…”
Section: Research Goals and Methodsmentioning
confidence: 99%
“…Ramírez‐Soto et al () describe a multipronged strategy to restore tropical montane cloud forest, focusing on the applied nucleation approach to forest restoration (Corbin & Holl ). We agree with Ramírez‐Soto et al () that all tropical forest restoration should include a careful diagnosis of the degree of land degradation prior to selecting a restoration strategy and the species to plant, monitoring of the efficacy of efforts, and active dissemination of information to and training of stakeholders. We write to highlight a factual error in one point and provide contrasting perspectives on two points in the article.…”
mentioning
confidence: 99%